2020
DOI: 10.1002/path.5399
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in gray and white matter multiple sclerosis lesions: impact on pathophysiology

Abstract: Multiple sclerosis (MS) is a chronic disease of the CNS, hallmarked by inflammation and demyelination. Early stages of the disease frequently show active lesions containing numerous foamy macrophages and inflammatory cells. Disease progression is highlighted by increasing numbers of mixed active/inactive or inactive lesions showing sparse inflammation and pronounced astrogliosis. Furthermore, gray matter lesions increase in number and extent during disease progression. MicroRNAs (miRNAs) comprise a group of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 130 publications
(203 reference statements)
0
13
0
Order By: Relevance
“…In this context, we explored three representative members of the let-7 family (let-7b-5p, let-7e-5p, let-7f-5p) in terms of CSF abundance and correlation with other 21 MS-related miRNAs as well as potential implications in MS disease. Although all let-7 miRNAs have the possibility to control miRNA biogenesis and functioning because they share the same repertoire of target mRNAs with a role in miRNA metabolism, we specifically identified let-7b-5p as a possible hub of a network of seven miRNAs highly linked to MS [54][55][56][57][58][59][60][61][62][63]74]. Neither let-7e-5p or let-7f-5p showed such strong correlations with other detected miR-NAs in the CSF, suggesting that the timing and cellular sources are as important as the target mRNA subset in MS regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we explored three representative members of the let-7 family (let-7b-5p, let-7e-5p, let-7f-5p) in terms of CSF abundance and correlation with other 21 MS-related miRNAs as well as potential implications in MS disease. Although all let-7 miRNAs have the possibility to control miRNA biogenesis and functioning because they share the same repertoire of target mRNAs with a role in miRNA metabolism, we specifically identified let-7b-5p as a possible hub of a network of seven miRNAs highly linked to MS [54][55][56][57][58][59][60][61][62][63]74]. Neither let-7e-5p or let-7f-5p showed such strong correlations with other detected miR-NAs in the CSF, suggesting that the timing and cellular sources are as important as the target mRNA subset in MS regulation.…”
Section: Discussionmentioning
confidence: 99%
“…More in detail, we observed strong and direct correlations (r > 0.5) between let-7b-5p and miR-451a (r = 0.84), miR-223-3p (r = 0.68), miR-92a-3p (r = 0.63) and miR-16-5p (r = 0.54). Interestingly, all these miRNAs have been implicated in MS as crucial regulators of the immune system [54][55][56][57][58][59] and/or CNS homeostasis [55,[60][61][62][63]. Similar considerations can be made about miRNAs that were milder correlated with let-7b-5p (0.4 < r ≤ 0.5), like miR-24-3p and miR-34a-5p, or with the remyelination-related miR-219-3p [36], suggesting that multiple but common cellular sources participate to their release into the CSF [6,64].…”
Section: Let-7b-5p Is a Possible Regulatory Hub Of The Pattern Of Ms-mentioning
confidence: 99%
“…There are fewer studies of miRNAs in MS lesions but these have nevertheless identified miRNAs regulating the resident CNS cells central to MS pathology (Junker et al, 2009;Noorbakhsh et al, 2011;Tripathi et al, 2019;Fritsche et al, 2020). Despite considerable lesion and neurological heterogeneity observed in MS, collated findings suggest that there are conserved miRNA profiles that influence gliosis, inflammation, demyelination and remyelination (Teuber-Hanselmann et al, 2020). Junker et al identified 20 upregulated and 8 downregulated miRNAs in active MS lesions compared to normal appearing white matter (NAWM) (Junker et al, 2009).…”
Section: Microglial Transcriptomics: the Link Between Genotype And Phenotypementioning
confidence: 99%
“…Ortholog genes share an evolutionary connection and usually present similar roles in different organisms, so some features of an ortholog gene from a particular species can support the understanding of this feature in another specie [28]. Studies demonstrated a correlation between mir186 expression in regulatory processes involved in the development of human disorders, such as hodgkin lymphoma [29], multiple sclerosis [30], hepatocarcinogen [31], and Head and neck squamous cell carcinoma [32].…”
Section: Differentially Expressed Mirnasmentioning
confidence: 99%